Enterococcal endocarditis: can we win the war? (2012)
Treatment of enterococcal infections has long been recognized as an important clinical challenge, particularly in the setting of infective endocarditis (IE). Furthermore, the increase prevalence of isolates exhibiting multidrug resistance (MDR) to traditional anti-enterococcal antibiotics such as ampicillin, vancomycin and aminoglycosides (high-level resistance) poses immense therapeutic dilemmas in hospitals around the world. Unlike IE caused by most isolates of Enterococcus faecalis, which still retain susceptibility to ampicillin and vancomycin, the emergence and dissemination of a hospital-associated genetic clade of multidrug resistant Enterococcus faecium, markedly limits the therapeutic options. The best treatment of IE MDR enterococcal endocarditis is unknown and the paucity of antibiotics with bactericidal activity against these organisms is a cause of serious concern. Although it appears that we are winning the war against E. faecalis, the battle rages on against isolates of multidrug-resistant E. faecium.